Why Some Students Fail to Complete Their Education (Journal of Education and Development, 2025)
Students must have strong cognitive skills in math and literacy, as well as the ability to solve problems, to succeed in a constantly evolving professional environment. Nevertheless, the UNESCO Institute for Statistics has reported that a global education crisis significantly impacts 617 million students (Montoya, 2018). Two-thirds of these students either drop out or remain in school without acquiring these fundamental skills, as they struggle with math and literacy. The crisis threatens their ability to secure better employment and escape poverty. The data from UNESCO indicates that 80% of students between the ages of 12 and 14 cannot read proficiently, a problem that affects students worldwide, including those in the United States and Europe. The dread of failure is a substantial factor that contributes to student failure. Although anxiety may serve as an incentive for certain students, it can also undermine their self-assurance and impede their advancement. Students who are apprehensive about failure may avoid challenges or withdraw prematurely. Another concern is inadequate preparation. Transitioning from elementary to secondary school and university necessitates emotional stability, intellectual abilities, and a readiness to study. Regrettably, a significant number of students experience feelings of being behind and may even resort to deception due to a lack of preparation. According to empirical research, plagiarism is common among college students (You et al., 2018). Moreover, dyslexia and dyscalculia are specific learning difficulties that impede reading comprehension and mathematical aptitude, respectively. Learning becomes more difficult for learners with ADHD due to its impact on executive functioning, impulse control, and concentration. These challenges can affect academic achievement, motivation, self-esteem, and social relationships. In conclusion, it is imperative to address the dread of failure, improve academic preparedness, and support students with learning disabilities to enhance educational outcomes.